STUDENTS’ PERCEPTIONS ON DEMOCRATIC CLASSROOM MANAGEMENT IN TERTIARY EDUCATION CONTEXT - Henny Mardiah (UIN Sumatera Utara, 2022)
This study focused on university students’ perceptions on democratic classroom management. This research investigated the effectiveness of democratic classroom management. The population of this study were the fifth semester students of class C1 of Muhammadiyah University of North Sumatera majoring in Primary School Teacher Education (PGSD). They consisted of 35 students. This research was conducted with qualitative method. The writer used questionnaire as the instrument of interview. The research findings indicated some important things. To begin with, students responded positive about democratic classroom management practices that have been implemented in the classroom for about 9 meetings. It means, the teacher has successfully practiced the democratic classroom management in her class. Next, knowing democratic classroom management helps university students to be more courageous, active and responsible for their own learning. They can express their ideas and opinions without being afraid to be judged. Lastly, for teachers, the student survey provides information to evaluate their own teaching practices, to improve the democratic classroom management style. Developing a democratic classroom management requires significant and consistent effort and in the joint work of teachers and active students through all stages of the teaching-learning process.